A Rare Case of Glycogen Storage Disease Type 1a Presenting with Hemophagocytic Lymphohistiocytosis (HLH) - Saneifard, Hedyeh (Case Rep Pediatr, 2020)
BACKGROUND: Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening hyperinflammatory syndrome characterized by fever, respiratory distress, massive hepatomegaly, and bicytopenia. It is classified into primary (congenital) and secondary (acquired) types. There are many diseases associated with secondary HLH, but glycogen storage disease is a novel cause of secondary HLH. Case Presentation. In this case, we present a five-month-old female infant with recurrent fever, poor feeding, pallor, and prolonged diarrhea for two months. With a diagnosis of HLH, the patient was treated with IVIG and prednisolone. After treatment was initiated, the patient's general condition improved. All metabolic workup was normal. We did whole-exome sequencing that confirmed glycogen storage disease (GSD) type 1. CONCLUSION: Metabolic diseases are one of the severe causes of secondary HLH in infants; hence, complete metabolic assessment is mandatory in these patients, and GSD must be included in the differential diagnosis of HLH metabolic causes.